Training programs in gender violence cases. An alternative penal measure, unknown and necessary - López de Zubiría Díaz, Sandra (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2017)
The entry into force of LO 1/2004 meant the establishment of new measures aimed at combating the phenomenon of gender violence, as well as providing it with the visibility and sensitization it required. Among the reforms it produced is the compulsory participation in rehabilitation programs in case of substitution or suspension of sentences for those convicted of gender-based violence. In spite of the importance of these rehabilitation programs, given that they are assigned to a not insignificant number of aggressors each year, we are faced with a reality that shows us various practical problems in the application of such programs, such as duration, the waiting list or approval control, among others, that d serve to be analyzed. The fight against gender violence must be focused both on prevention and treatment, and this is why the study of rehabilitation programs should not be overlooked. The present text will reflect on the relevance of counting on this type of alternative measures and on the need to improve the study of rehabilitation programs, currently persecuted by unfounded scarce recognition and criticism, to which we must add the objective difficulties of implementation, which make it impossible to effectively achieve its objectives.